Overview of Stress Levels among Elderly Caregivers in Japan - Irma Amalia; Eska Dwi Prajayanti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: This study aimed to describe the stress levels experienced by Indonesian elderly caregivers (nurses) working in Japan, with a focus on their demographic characteristics and psychological well-being. Method: A descriptive quantitative design was applied to portray stress without examining relationships among variables. The population comprised 51 Indonesian caregivers, all of whom were included as respondents using a total sampling technique. Data were collected online from July to August 2025 through a validated 12-item Zarit Burden Interview questionnaire and analyzed with descriptive statistics using SPSS. Demographic information such as gender and age was also obtained. Result: Results revealed that most respondents were female (88.2%) and in the 26–35 age group (52.9%). Stress level analysis showed that 39.2% experienced low stress, 41.2% moderate stress, and 19.6% high stress. These findings indicate that while most caregivers manage caregiving demands adequately, a significant proportion experiences moderate to high stress that may affect health and job performance. Conclusion: The study concludes that gender, age, and workplace conditions are key determinants of caregiver stress and recommends targeted mental health interventions, supportive workplace policies, and stress management training to reduce psychological burdens. Future research should incorporate longitudinal and mixed-method approaches to identify causal factors and coping mechanisms to better inform preventive strategies.